Coping Mechanism in Women with Breast Cancer - Titis Eka Apriliyanti; Kusnanto Kusnanto; Joko Suwito; Abdul Fauzi (STIKes Patria Husada Blitar, 2019)
Background: Impaired coping mechanisms often occur in women with breast cancer. The purpose of this study is to determine the description of coping mechanisms in women with breast cancer who undergo chemorepy, radiation or both.Methods: The population in this study were women with breast cancer who underwent chemotherapy, radiation or both. Sampling was done by random sampling where the number of samples is 70. Taking data using the COPE Brief instrument.Result: Four indicators in the destructive category were acceptance (54.3%), denial (61.4%), emotional support (52.9%) and positive reframing (67.1%) while three indicators were mostly in the constructive category, namely self blame (60%), active (64.3) %), and Behavioral disengagement (72.9%).Conclusion: Four destructive indicators indicate poor avoidance and positive thinking in breast cancer patients, while 3 constructive indicators describe good problem solving. Assessment based on this indicator can be taken into consideration in the selection of appropriate interventions to improve coping mechanisms in breast cancer patients.